Adolescent HPV vaccination: empowerment, equity and ethics. Issue 8 (2nd August 2020) - Sundaram, Neisha; Voo, Teck Chuan; Tam, Clarence C.
ABSTRACT: Despite the great promise offered by human papillomavirus (HPV) vaccines to reduce disease burden and promote socioeconomic and gender equality, their implementation into national programmes has been slow. The vaccination of adolescents against a disease that may have serious consequences much later in life requires special consideration to the principles and processes of informed consent. Accumulating experiences from implementations in many countries indicate a need to examine ethical considerations related to adolescent vaccination. However, frameworks that integrate legal, development- and rights-based considerations in adolescent vaccination policies, while taking into account practical realities of HPV vaccination programmes, are currently lacking. We argue that principles of autonomy, social justice and gender equality have impacts on adolescent immunization that go beyond mere acceptance of vaccination and place greater demands on what constitutes meaningful informed consent, with implications for the provision of age- and context-appropriate information, vaccine financing and gender-based vaccination policies. Independent of cost-effectiveness considerations, we find a strong case to support universal HPV vaccination of girls that is free at the point of use and, where feasible, to extend vaccination to boys under the same financing schemes. Abbreviations: HPV: Human papillomavirus; STI: Sexually transmitted infections; WHO: World Health Organization